Association of positive psychological variables with disease activity, functional disability and erythrocyte sedimentation rate in patients with rheumatoid arthritis: a preliminary study - K.C. Meléndez-Monreal; A.J.L. Brambila-Tapia; V. González-Díaz; S. Cerpa-Cruz; S.R. Gutiérrez-Ureña; M.d.C. Yeo-Ayala; R. Robles-García; G.E. Martínez-Bonilla (PAGEPress Publications, 2023)
Rheumatoid arthritis (RA) is a chronic autoimmune disease which has shown positive correlations between negative psychological variables and disease activity in transversal studies and in the follow-up. However, the association of positive psychological variables with disease parameters including disease activity (DAS-28), functional disability (HAQ) and erythrocyte sedimentation rate (ESR) has not been investigated. Patients with RA attending the external consultation of a third level hospital were invited to participate and fill in a questionnaire with personal, disease and psychological variables; body mass index was also obtained as well as ESR. A total of 49 patients were included. The three dependent variables correlated among them, with the highest correlation for DAS-28 and HAQ (r=0.645, p<0.01), followed by somatization and HAQ (r=0.614, p<0.01) or DAS-28 (r=0.537, P<0.01). In addition, HAQ showed negative correlations with environmental mastery (r=- 0.366, p<0.01), personal growth (r=-0.292, p<0.05) and monthly extra money (r=-0.328, p<0.05), and borderline negative correlations with emotion perception (r=-0.279, p=0.053) and self-acceptance (r=-0.250, p=0.08). ESR showed a significant negative correlation with emotion perception (r=-0.475, p<0.01). In conclusion, we observed important correlations of positive psychological variables with disease activity, functional disability and ESR that could be addressed in order to prevent or treat these disease features.